2006
DOI: 10.1016/j.cub.2006.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Auditory and Visual Bistability Reveal Common Principles of Perceptual Organization

Abstract: When dealing with natural scenes, sensory systems have to process an often messy and ambiguous flow of information. A stable perceptual organization nevertheless has to be achieved in order to guide behavior. The neural mechanisms involved can be highlighted by intrinsically ambiguous situations. In such cases, bistable perception occurs: distinct interpretations of the unchanging stimulus alternate spontaneously in the mind of the observer. Bistable stimuli have been used extensively for more than two centuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
369
8
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(411 citation statements)
references
References 42 publications
33
369
8
1
Order By: Relevance
“…For tristable perception (first two groups of bars), durations differed significantly: F(2, 578) ¼ 104, p , 10 -15 , effect size (partial h 2 ) p h 2 ¼ 0.27 (290 trials included). The first coherent percept was longer than the subsequent coherent percepts (what we called the inertia of the first percept), as observed previously [16,27,29,30]. That was not the case for bistable perception due to occlusion: F(2, 572) ¼ 4.8, p ¼ 0.009, p h 2 ¼ 0.016 (287 trials included; the p-value is significant but the very small effect size indicates that the difference is in fact negligible; moreover, it is only due to a minor difference between the second and the third coherent percepts).…”
Section: (B) Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…For tristable perception (first two groups of bars), durations differed significantly: F(2, 578) ¼ 104, p , 10 -15 , effect size (partial h 2 ) p h 2 ¼ 0.27 (290 trials included). The first coherent percept was longer than the subsequent coherent percepts (what we called the inertia of the first percept), as observed previously [16,27,29,30]. That was not the case for bistable perception due to occlusion: F(2, 572) ¼ 4.8, p ¼ 0.009, p h 2 ¼ 0.016 (287 trials included; the p-value is significant but the very small effect size indicates that the difference is in fact negligible; moreover, it is only due to a minor difference between the second and the third coherent percepts).…”
Section: (B) Resultssupporting
confidence: 79%
“…Interestingly, in all of the published data, after the initial build up, the probability of hearing two streams stabilizes below 100%. As pointed out by Pressnitzer & Hupé [16], this indicates that there are subsequent perceptual alternations back and forth to a one-stream percept after the initial build up. Perceptual reports for long-lasting sequences confirmed that streaming was indeed a bistable phenomenon [16][17][18].…”
Section: Introductionmentioning
confidence: 68%
“…If the frequency separation is less than a (smaller) critical value, called the fission boundary (FB [2]), a single stream is usually heard, even when the subject is instructed to try to hear two streams. However, even for very small or very large frequency separations, the percept may flip if the sequence is presented for a long time [3,17]. In other words, bistability occurs.…”
Section: The Build-up Resetting and Decay Of Stream Segregation (A)mentioning
confidence: 99%
“…For instance, a steady patch of light displayed extra-foveally eventually fades away from perception ( Troxler 1804); when presented with a steady ambiguous stimulus, perception oscillates between the possible perceptual interpretations whether in vision (e.g. the Necker cube) or in audition (Pressnitzer & Hupé 2006). Llinás et al (1998) remarked that external stimulations act as modulations of ongoing activity not as triggers of brain activity: activity at a given instant incorporates and is partially determined by the system state just prior to this instant.…”
Section: Shuffling Time In the Brainmentioning
confidence: 99%